1998
DOI: 10.1007/s004250050408
|View full text |Cite
|
Sign up to set email alerts
|

Fusion and fission of plasma-membrane material accommodates for osmotically induced changes in the surface area of guard-cell protoplasts

Abstract: Stomatal movement requires large and repetitive changes in cell volume and consequently changes in surface area. The patch-clamp technique was used to monitor changes in plasma-membrane surface area of individual guard-cell protoplasts (GCPs) by measuring membrane capacitance (C m ), a parameter proportional to the surface area. The membrane capacitance increased under hypoosmotic conditions and decreased after hypertonic treatment. As the speci®c capacitance remained constant, this demonstrates that osmotical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
80
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 19 publications
3
80
0
Order By: Relevance
“…Furthermore, it has been shown that the cross-sectional shape of guard cells is nearly circular at high turgor pressures, but becomes more flattened as they lose turgor (Raschke, 1979). This lends credibility to the first solution because flattening could produce changes in volume while maintaining a constant surface area.The problem of how guard cells maintain the integrity of the plasma membrane during volume changes has been addressed using osmotically induced changes in the volume of guard cell protoplasts (Homann, 1998;Kubitscheck et al, 2000). Those studies showed that vesicles were internalized 1 This work was supported by the National Science Foundation (grant no.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been shown that the cross-sectional shape of guard cells is nearly circular at high turgor pressures, but becomes more flattened as they lose turgor (Raschke, 1979). This lends credibility to the first solution because flattening could produce changes in volume while maintaining a constant surface area.The problem of how guard cells maintain the integrity of the plasma membrane during volume changes has been addressed using osmotically induced changes in the volume of guard cell protoplasts (Homann, 1998;Kubitscheck et al, 2000). Those studies showed that vesicles were internalized 1 This work was supported by the National Science Foundation (grant no.…”
mentioning
confidence: 99%
“…Thus, guard cells must either: (a) change shape such that plasma membrane surface area remains nearly constant while volume changes, or (b) move membrane between the plasma membrane and internal sources within the cell to accommodate changes in surface area. Although the literature on guard cells assumes the latter solution (Diekmann et al, 1993;Homann, 1998;Blatt, 2000), examples of both solutions can be found in animal cells. For example, mammalian erythrocytes change shape to maintain a constant surface area as volume is changed osmotically, but neurons continuously shuttle membrane between the endomembrane system and the plasma membrane to vary both surface area and volume (Morris and Homann, 2001).…”
mentioning
confidence: 99%
“…Very modest hydrostatic pressures gave rates of capacitance rise 50-fold higher than under elevated [Ca# + ] i without evidence of saturation and, in Vicia guard cell protoplasts, was insensitive to [Ca# + ] i (Homann, 1998). These results suggest a much larger pool of vesicles ready for fusion and\or their rapid supply to the plasma membrane, by contrast with secretion evoked by [Ca# + ] i .…”
Section: Coupling Secretion To Cytosolic-free Ca# + Concentrationmentioning
confidence: 83%
“…Secretion activity independent of [Ca# + ] i has been intimated from work with barley aleurone protoplasts (Homann & Tester, 1997) and more recently in studies of guard cell protoplasts (Homann, 1998) and maize coleoptile protoplasts (Thiel et al, 1999). Homann & Tester (1997) found a small, but steady rise in capacitance that was independent of [Ca# + ] i level in the patch pipette.…”
Section: Coupling Secretion To Cytosolic-free Ca# + Concentrationmentioning
confidence: 99%
See 1 more Smart Citation